Wisdom as a Buffer Against Experiential Avoidance's Impact on Relationship Satisfaction - Jafari, Zeynolabedin; Jafari, MohammadBagher (KMAN Counseling & Psychology Nexus, 2023)
This study aims to explore the predictive relationship between wisdom, experiential avoidance, and couples' adjustment, hypothesizing that wisdom can mitigate the negative effects of experiential avoidance on relationship satisfaction. Utilizing a cross-sectional design, 250 participants completed the Self-Assessed Wisdom Scale (SAWS), Acceptance and Action Questionnaire-II (AAQ-II), and Dyadic Adjustment Scale (DAS). Data were analyzed through linear regression to examine the impacts of wisdom and experiential avoidance on couples' adjustment. The analysis revealed that wisdom positively predicts couples' adjustment, offering a protective effect against the detrimental impacts of experiential avoidance on relationship satisfaction. Specifically, wisdom accounted for a significant variance in couples' adjustment, while higher experiential avoidance was associated with lower relationship satisfaction. The study underscores the importance of wisdom in enhancing couples' adjustment and mitigating the negative effects of experiential avoidance. These findings suggest the potential for interventions targeting wisdom and experiential avoidance to foster healthier relationship dynamics.